A method for preparing biodiesel from bio-oil

Through the complex catalysts prepared by the zigzag particles, the problem of being disturbed by water by hydrogenation catalysts in high temperature and high pressure environments, and realizing the stability of the catalyst and the improvement of product cleaning.

CN118995283BActive Publication Date: 2025-01-28LUOYANG HENGJIU BIOENERGY CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411496956.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

In a high-temperature and high-pressure biodiesel preparation environment, existing hydrogenation catalysts are easily invaded by by-product water, resulting in a reduced catalytic effect and the active sulfur components are easily dissipated, affecting the cleanliness of the product and the stability of the catalyst.

Method used

The recreational catalyst is used to prepare catalysts with water absorption structure by impregnating, pores and acid decoration treatment of the zigza particles. This catalyst absorbs water molecules through acid decoration of amporogenic microspheres, and reduces its dispersion through iron oxide fixed active sulfur components.

Benefits of technology

It improves the efficiency of biological oil and hydrogenation, reduces the possibility of catalyst activity affected by water, enhances the stability of the catalyst and the cleaning of products, and reduces the impurities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118995283B_ABST
    Figure CN118995283B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of biodiesel synthesis, and specifically discloses a method for preparing biodiesel from bio-oil. It includes the following steps: (S01) hydrogenation pretreatment; (S02) hydrogenation refining; (S03) hydrogenation isomerization; and finally biodiesel is obtained. The preparation steps of the composite catalyst are: (a) zeolite impregnation treatment: zeolite particles are mixed with ferric chloride solution, and ferric chloride impregnated zeolite is obtained after drying; (b) preparation of zeolite microspheres: ferric chloride impregnated zeolite, adhesive, and pore-forming agent are mixed evenly, granulated, sintered, and zeolite microspheres are obtained; (c) zeolite microsphere acid modification treatment: zeolite microspheres are added to mixed acid, and acid-modified zeolite microspheres are separated; (d) catalyst mixing treatment: acid-modified zeolite microspheres are mixed with alumina-supported sulfided Co-Ni hydrogenation catalyst to obtain a composite catalyst. The composite catalyst has a stable catalytic benefit and can reduce the influence of catalytic byproduct water on the catalytic activity of the hydrogenation catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of biodiesel synthesis, and more specifically, to a method for preparing biodiesel from bio-oil. Background Art

[0002] Biodiesel refers to a diesel-like oil product obtained from waste animal and plant oils and fats through ester exchange or catalytic hydrogenation processes. Among them, fatty acid ester biodiesel obtained through ester exchange is called the first generation of biodiesel, and hydrocarbon biodiesel obtained through catalytic hydrogenation is called the second generation of biodiesel. The first generation of biodiesel has limitations in application due to its high oxygen content, incomplete combustion, and low energy conversion efficiency. Compared with the first generation of biodiesel, the second generation of biodiesel is mainly hydrocarbons with a low oxygen content. The products after full combustion are mainly water and carbon dioxide. The products are clean and have high energy utilization efficiency, so it has become a research focus in recent years.

[0003] In the preparation process of second-generation biodiesel, the role of hydrogenation catalyst is crucial. The specific principle of catalytic hydrogenation is that in the hydrogenation reactor, oil molecules are adsorbed on the active sites of the catalyst, hydrogenation reaction occurs, fatty acids are converted into saturated hydrocarbons, and finally the saturated hydrocarbon products are desorbed from the active sites of the catalyst and collected to obtain biodiesel with diesel properties.

[0004] The catalytic hydrogenation reaction process requires the catalyst to have strong reactivity in order to achieve a higher material conversion efficiency of the raw materials. Currently, the commonly used non-precious metal hydrogenation catalysts are mainly sulfide-loaded metal catalysts such as Co, Ni, and Mo. Due to their low cost and high catalytic efficiency, they have broad application prospects. However, this type of catalyst is easily invaded by the catalytic byproduct water in the high-temperature and high-pressure reaction environment of biodiesel preparation, resulting in a problem of reduced catalytic effect. At the same time, the active sulfur component in the catalyst is also easily dissipated due to dissolved water, so the catalytic effect is not stable. How to improve the catalyst and obtain a catalyst that can continuously and stably exert a catalytic effect still has certain technical difficulties.

[0005] The Chinese patent application document with application publication number CN117660115A discloses a method for preparing bio-based long-chain alkanes, which regulates the directional demethanolation and decarbonylation process of bio-oil by preparing a series of acid, base and supported catalysts. By changing the deoxygenation path, the generation of water in the process is reduced, alleviating the negative impact of water on the catalyst.

[0006] Although the above application documents attempt to reduce the impact of byproduct water on the catalyst, the catalyst prepared in the scheme is too complicated, and the fine control of the catalytic process also increases the cost of industrial production. At the same time, the deactivation problem caused by the intrusion of water into the catalyst has not been completely solved, so the need to find a long-lasting and stable hydrogenation catalyst still exists. Summary of the invention

[0007] In order to further improve the situation that the catalytic efficiency of the hydrogenation catalyst decreases with the accumulation of byproduct water, and reduce the pollution of the product by the escape of active sulfur components in the hydrogenation catalyst, the present application provides a method for preparing biodiesel from bio-oil, which adopts the following technical solution:

[0008] (S01) Hydrogenation pretreatment: Bio-oil is mixed with hydrogen and added into a reactor loaded with a composite catalyst to react and obtain hydrogenated oil;

[0009] (S02) Hydrofining: The hydrogenated oil is mixed with hydrogen and added into the first fixed bed loaded with the composite catalyst to react and obtain refined oil;

[0010] (S03) Hydroisomerization: The refined oil is mixed with hydrogen and added to the second fixed bed loaded with palladium mesoporous carbon catalyst to react to obtain isomerized oil, which is then fractionated at atmospheric pressure to obtain biodiesel on the distillation line side;

[0011] The composite catalyst preparation comprises the following steps:

[0012] (a) Zeolite impregnation treatment: immersing zeolite particles in a ferric chloride solution, stirring, and drying to obtain ferric chloride impregnated zeolite;

[0013] (b) Preparation of zeolite microspheres: ferric chloride impregnated zeolite, a binder, and a pore former are uniformly mixed, granulated, and sintered to obtain zeolite microspheres;

[0014] (c) Acid modification treatment of zeolite microspheres: adding zeolite microspheres to a mixed acid for treatment, and then performing solid-liquid separation to obtain acid-modified zeolite microspheres;

[0015] (d) Catalyst mixing treatment: The acid-modified zeolite microspheres are mixed with the alumina-supported sulfided Co-Ni hydrogenation catalyst to obtain a composite catalyst.

[0016] By adopting the above technical scheme, using the prepared composite catalyst to prepare biodiesel, the efficiency of bio-oil hydrogenation conversion can be improved. Acid-modified zeolite microspheres in the composite catalyst play a vital role. On the one hand, there are hydroxyl structures on the surface and inside of the acid-modified zeolite microspheres, which can form hydrogen bonds with polar water molecules. This structure can be used to absorb the water generated by the catalytic reaction on the surface of the alumina-supported sulfided Co-Ni hydrogenation catalyst. At the same time, the adsorbed water is introduced into the interior of the zeolite through the acid-modified zeolite micropores, enhancing the adsorption effect of the microspheres on water. On the other hand, the ferric chloride doped in the zeolite is converted into ferric oxide during the high-temperature sintering process, which can absorb the scattered active sulfur components and reduce the content of impurities in biodiesel.

[0017] Preferably, the temperature of the zeolite impregnation treatment is set at 45-50°C.

[0018] By adopting the above technical solution, in a mixed solvent environment, by testing a series of temperatures, the applicant found that the loading amount of iron ions in zeolite is approximately a function related to temperature. By fitting the experimental data using Origin, the fitted function equation can be expressed as: W=-0.00001539T 2 +0.12T+27.59, W represents the loading amount in percentage (%), and T represents the thermodynamic temperature under experimental conditions in Kelvin (K). When the immersion temperature is between 45-50°C, the loading amount curve is in the rising area, and the iron ion loading effect is the best.

[0019] Preferably, the mass ratio of the ferric chloride impregnated zeolite to the pore-forming agent is (100-110):(1-1.2).

[0020] By adopting the above technical solution and adjusting the sintering temperature and time, the obtained zeolite microspheres can achieve the expected expansion percentage of 115%-125%. Within this mass ratio range, the zeolite is in the best condition.

[0021] Preferably, the pore-forming agent is carbon powder.

[0022] By adopting the above technical solution, carbon powder is used as a pore-forming agent, and has an excellent mixing effect when mixed with ferric chloride impregnated zeolite and a binder. The zeolite microspheres obtained after sintering have a certain supporting strength and are less likely to be destroyed.

[0023] Preferably, the sintering temperature of the zeolite microspheres is set to 600-620° C. and kept warm for 5 hours.

[0024] By adopting the above technical solution, the carbon powder in the zeolite microspheres is removed in the form of CO2 in the high-temperature environment of granulation, thereby forming holes and channels inside and on the surface of the zeolite microspheres. The applicant found in the experiment that when the sintering temperature range is 600-620°C and the temperature is kept for 5 hours, the zeolite microspheres have the best pore-forming effect and the lowest breakage rate. When the temperature is lower than 600°C, the expansion of the zeolite microspheres is only equivalent to 105%-110% of the volume of the zeolite microspheres before calcination, which is lower than the average expansion volume of 120% in the temperature range of 600-620°C. It shows that when the calcination temperature is lower than 600°C, the degree of conversion of the carbon powder mixed in the zeolite microspheres into CO2 is low. At the same time, the residual carbon powder will also block the formed channels and weaken the pore-forming effect. When the temperature is higher than 620°C, after the calcined product is filtered through a fine-pore filter screen, the amount of zeolite microspheres with smaller particle size increases, and the amount of this product increases with increasing temperature and reaction time, indicating that the zeolite microspheres are broken, which is not conducive to the adsorption of water. Therefore, it is necessary to limit the temperature and reaction time.

[0025] Preferably, the mixed acid is prepared by mixing 1 mol / L hydrochloric acid and 1.5 mol / L sulfuric acid in a volume ratio of (1.5-2):1.

[0026] By adopting the above technical solution, the pores in the zeolite microspheres can be further enlarged and the pores with defects existing in the pore-making process can be modified. Acid modification can also make the pores more uniform, and uniform pores can enhance the adsorption effect of zeolite microspheres.

[0027] Preferably, the time for the acid modification treatment of the zeolite microspheres is set to 15-20 minutes.

[0028] By adopting the above technical solution, within this treatment time range, the surface state of the obtained acid-modified zeolite microspheres is optimal.

[0029] Preferably, the temperature of the zeolite microsphere acid modification treatment is set to 40-45°C.

[0030] By adopting the above technical solution, the adsorption effect of the acid-modified zeolite microspheres is further improved.

[0031] Preferably, in the composite catalyst, the mass percentage of the acid-modified zeolite microspheres in the composite catalyst is 25%-35%.

[0032] By adopting the above technical solution, the compounding effect of acid-modified zeolite microspheres and alumina-supported sulfided Co-Ni hydrogenation catalyst is the best. When the mass percentage of acid-modified zeolite microspheres in the compound catalyst increases from 1% to 25%, the catalytic effect of the compound catalyst is also increased. This is because the water byproducts produced by the catalysis are well absorbed by the acid-modified zeolite microspheres. When the mass percentage of acid-modified zeolite microspheres in the catalytic system is 25%-35%, the generation and absorption of water approximately reach a state of equilibrium, and the compound catalytic effect is the best. When the percentage of acid-modified zeolite microspheres in the compound catalyst further increases, the use effect of the compound catalyst decreases.

[0033] In summary, this application has the following beneficial effects:

[0034] 1. The present application adopts the method of impregnation, pore formation and acid modification of zeolite particles to obtain a water-absorbing structure. The structure has a good adsorption effect on catalytic byproduct water, can absorb water molecules accumulated on the surface of hydrogenation catalyst due to catalytic action, reduce the influence of water on catalyst activity, and weaken the water dissolution and loss rate of active sulfur components in the catalyst.

[0035] 2. In this application, it is preferred to use ferric chloride to impregnate zeolite, and the ferric chloride is converted into ferric oxide after sintering as a sulfur-fixing agent in the catalytic system. For the water-soluble H2S component in the active sulfur component of the catalyst, the ferric oxide can undergo an adsorption reaction with the H2S component, and the reaction equation is: , thereby fixing the S element and reducing the escape of sulfur components and contamination of the product.

[0036] 3. The composite catalyst of the present application is used to absorb byproduct water and escaped active sulfur through the combined action of zeolite microspheres and iron oxide, thereby improving the catalytic efficiency of the composite catalyst and reducing the interference of impurity S in the hydrogenation product on the product. When the catalytic reaction is complete, the acid-modified zeolite microspheres in the composite catalyst undergo a desorption reaction after oxygenation heat treatment to restore the adsorption effect. The specific equation of the desorption reaction is: , thereby realizing the reuse of the composite catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Process flow for preparing biodiesel from bio-oil.

[0038] Figure 2 It is the conversion rate of hydrogenated oil and refined oil obtained during the conversion of oil samples in Examples 1-3 and Comparative Examples 1-2.

[0039] Figure 3 It is the sulfur content and water content in the samples obtained after the oil samples are converted in Example 1-3 and Comparative Example 1-2. DETAILED DESCRIPTION

[0040] Example 1

[0041] The method for preparing biodiesel from bio-oil in this embodiment is as follows:

[0042] (S01) Hydrogenation pretreatment: 50 mL of bio-oil and hydrogen were mixed at a volume ratio of 300:1 and added into a reactor loaded with 25 g of composite catalyst at a pressure of 7 MPa, a temperature of 200 °C, and a space velocity of 0.3 h -1 , the hot high-separation oil circulation pump circulation ratio is 1:1, the reaction is 3h, and hydrogenated oil is obtained;

[0043] (S02) Hydrogenation refining: Hydrogenated oil and hydrogen were mixed in a volume ratio of 200:1 and added to the first fixed bed loaded with 20g of composite catalyst. The kettle pressure was 4MPa, the temperature was 200℃, and the air velocity was 0.3h -1 , react for 5 hours, and then use the stripping tower to desulfurize to obtain refined oil;

[0044] (S03) Hydroisomerization: Refined oil and hydrogen were mixed in a volume ratio of 200:1 and added to the second fixed bed loaded with 15 g of palladium mesoporous carbon catalyst. The reactor pressure was 4 MPa, the temperature was 250 °C, and the space velocity was 0.5 h -1 , react for 1.5h to obtain isomerized oil, which is then fractionated at normal pressure to obtain biodiesel on the distillation line side.

[0045] The preparation steps of the composite catalyst in this embodiment are as follows:

[0046] (a) Zeolite impregnation treatment: 10.5 g of zeolite particles with an average particle size of 1 mm were taken and immersed in 25 mL of 1 mol / L ferric chloride solution with a magnetic stirring speed of 50 rpm and a temperature of 45°C for 2 h. The remaining solvent was removed by filtration, and the filtered precipitate was transferred to an oven and dried at 60°C for 3 h. The precipitate was re-crushed to obtain ferric chloride-impregnated zeolite.

[0047] (b) Preparation of zeolite microspheres: 8.4 g of zeolite impregnated with ferric chloride was mixed with 0.1 g of pore-forming agent and put into a sugar coating machine. The zeolite impregnated with ferric chloride was mixed with the pore-forming agent and treated with a binder spray. The speed range of the instrument was then adjusted to 45 r / min. Mixed microspheres with a diameter of 3 mm were obtained by rolling and sieving. The mixed microspheres were then transferred to a reactor. The system temperature was controlled to be 600 °C and the pressure was 0.12 MPa. The reaction was carried out under high temperature and low pressure for 5 h. The zeolite microspheres with a particle size of 4 mm were obtained by filtering with a fine-pore filter.

[0048] (c) Acid modification of zeolite microspheres: 0.5 g of the zeolite microspheres prepared in step (b) were taken and put into 5 mL of mixed acid solution for treatment. The system temperature was controlled at 40°C and the magnetic stirring speed was 150 rpm. The acid treatment was carried out for 15 min, and then the microspheres were rinsed with deionized water for 2-3 times to remove the residual acid components. After drying, the acid-modified zeolite microspheres were obtained.

[0049] (d) Catalyst mixing: 5 g of acid-modified zeolite microspheres and 15 g of alumina-supported sulfided Co-Ni hydrogenation were uniformly mixed to obtain a composite catalyst.

[0050] Among them, bio-oil (oleic acid and linoleic acid 73.8wt%, stearic acid and other unsaturated fatty acids 21.3wt%) was obtained from waste cooking oil after filtering and deslagging pretreatment. Palladium mesoporous carbon catalyst (model: Pd102, palladium content 3.5%, specific surface area 350cm 2 / g) is produced by Xi'an Kaili New Materials Co., Ltd. Zeolite particles (specific surface area of ​​780m 2 / g, with a silicon dioxide content of 97.5%) was produced by Chaoyang Xinhe Zeolite Technology Co., Ltd. The pore-forming agent was a mixture of 300-mesh carbon powder and 600-mesh carbon powder in a mass ratio of 1:1. The binder was a mixture of sodium silicate, deionized water, and urea in a mass ratio of 15:1:20. The mixed acid solution was a mixture of 1 mol / L hydrochloric acid and 1.5 mol / L sulfuric acid in a volume ratio of 1.5:1.

[0051] Example 2

[0052] The method for preparing biodiesel from bio-oil in this embodiment is as follows:

[0053] (S01) Hydrogenation pretreatment: 50 mL of bio-oil and hydrogen were mixed at a volume ratio of 400:1 and added into a reactor loaded with 25 g of composite catalyst at a reactor pressure of 7 MPa, a temperature of 250 °C, and a space velocity of 0.5 h -1 , the hot high-separation oil circulation pump circulation ratio is 2:1, the reaction is 3h, and hydrogenated oil is obtained;

[0054] (S02) Hydrogenation refining: Hydrogenated oil and hydrogen were mixed in a volume ratio of 300:1 and added to the first fixed bed loaded with 20g of composite catalyst, with a kettle pressure of 5MPa, a temperature of 275℃, and a space velocity of 0.5h -1 , react for 5 hours, and then use the stripping tower to desulfurize to obtain refined oil;

[0055] (S03) Hydroisomerization: Refined oil and hydrogen were mixed at a volume ratio of 500:1 and added to the second fixed bed loaded with 15 g of palladium mesoporous carbon catalyst. The reactor pressure was 5 MPa, the temperature was 300 °C, and the space velocity was 0.75 h -1 , react for 1.5h to obtain isomerized oil, and after atmospheric pressure distillation, biodiesel is obtained on the distillation line side.

[0056] The preparation steps of the composite catalyst in this embodiment are as follows:

[0057] (a) Zeolite impregnation treatment: Weigh 10.5 g of zeolite particles with an average particle size of 1.5 mm and impregnate them in 25 mL of 1 mol / L ferric chloride solution with a magnetic stirring speed of 50 rpm and a temperature of 50°C for 2 h. Filter to remove the remaining solvent, then transfer the filtered precipitate to an oven and dry it at 60°C for 3 h, and re-crush it to obtain ferric chloride-impregnated zeolite.

[0058] (b) Preparation of zeolite microspheres: 10 g of zeolite impregnated with ferric chloride was mixed with 0.1 g of pore-forming agent and put into a sugar coating machine. The zeolite impregnated with ferric chloride was mixed with the pore-forming agent and treated with a binder spray. The speed range of the instrument was then adjusted to 45 r / min. Mixed microspheres with a diameter of 3.5 mm were obtained by rolling and sieving. The mixed microspheres were then transferred to a reactor. The system temperature was controlled to be 610 °C and the pressure was 0.12 MPa. The reaction was carried out under high temperature and low pressure for 5 h. The zeolite microspheres with a particle size of 4.5 mm were obtained by filtering with a fine-pore filter.

[0059] (c) Acid modification of zeolite microspheres: 0.5 g of the zeolite microspheres prepared in step (b) were taken and put into 5 mL of mixed acid solution for treatment. The system temperature was controlled at 45°C and the magnetic stirring speed was 150 rpm. The acid treatment was carried out for 15 min, and then the microspheres were rinsed with deionized water for 2-3 times to remove the residual acid components. After drying, the acid-modified zeolite microspheres were obtained.

[0060] (d) Catalyst mixing: 6 g of acid-modified zeolite microspheres and 14 g of alumina-supported sulfided Co-Ni hydrogenation were uniformly mixed to obtain a composite catalyst.

[0061] Among them, bio-oil (oleic acid and linoleic acid 73.8wt%, stearic acid and other unsaturated fatty acids 21.3wt%) was obtained from waste cooking oil after filtering and deslagging pretreatment. Palladium mesoporous carbon catalyst (model: Pd102, palladium content 3.5%, specific surface area 350cm 2 / g) is produced by Xi'an Kaili New Materials Co., Ltd. Zeolite particles (specific surface area of ​​780m 2 / g, with a silicon dioxide content of 97.5%) was produced by Chaoyang Xinhe Zeolite Technology Co., Ltd. The pore-forming agent was a mixture of 300-mesh carbon powder and 600-mesh carbon powder in a mass ratio of 1:1. The binder was a mixture of sodium silicate, deionized water, and urea in a mass ratio of 15:1:20. The mixed acid solution was a mixture of 1 mol / L hydrochloric acid and 1.5 mol / L sulfuric acid in a volume ratio of 2:1.

[0062] Example 3

[0063] The method for preparing biodiesel from bio-oil in this embodiment is as follows:

[0064] (S01) Hydrogenation pretreatment: 50 mL of bio-oil and hydrogen were mixed at a volume ratio of 500:1 and added into a reactor loaded with 25 g of composite catalyst at a reactor pressure of 10 MPa, a temperature of 250 °C, and a space velocity of 0.5 h -1 , the hot high-separation oil circulation pump circulation ratio is 2:1, the reaction is 3h, and hydrogenated oil is obtained;

[0065] (S02) Hydrogenation refining: Hydrogenated oil and hydrogen were mixed in a volume ratio of 800:1 and added to the first fixed bed loaded with 20g of composite catalyst, with a kettle pressure of 10MPa, a temperature of 275℃, and a space velocity of 0.5h -1 , react for 5 hours, and then use the stripping tower to desulfurize to obtain refined oil;

[0066] (S03) Hydroisomerization: Refined oil and hydrogen were mixed in a volume ratio of 700:1 and added to the second fixed bed loaded with 15g of palladium mesoporous carbon catalyst. The reactor pressure was 7MPa, the temperature was 350℃, and the space velocity was 1h -1 , react for 1.5h to obtain isomerized oil, and after atmospheric pressure distillation, biodiesel is obtained on the distillation line side.

[0067] The preparation steps of the composite catalyst in this embodiment are as follows:

[0068] (a) Zeolite impregnation treatment: Weigh 10.5 g of zeolite particles with an average particle size of 2 mm and impregnate them in 25 mL of 1 mol / L ferric chloride solution with a magnetic stirring speed of 50 rpm and a temperature of 50°C for 2 h. Filter to remove the remaining solvent, then transfer the filtered precipitate to an oven and dry it at 60°C for 3 h, and re-crush it to obtain ferric chloride-impregnated zeolite.

[0069] (b) Preparation of zeolite microspheres: 11 g of zeolite impregnated with ferric chloride was mixed with 0.1 g of pore-forming agent and put into a sugar coating machine. The zeolite impregnated with ferric chloride was mixed with the pore-forming agent and treated with a binder spray. The speed range of the instrument was then adjusted to 45 r / min. Mixed microspheres with a diameter of 4 mm were obtained by rolling and sieving. The mixed microspheres were then transferred to a reactor. The system temperature was controlled to be 620°C and the pressure to be 0.12 MPa. The reaction was carried out under high temperature and low pressure for 5 h. The zeolite microspheres with a particle size of 5 mm were obtained by filtering with a fine-pore filter.

[0070] (c) Acid modification of zeolite microspheres: 0.5 g of the zeolite microspheres prepared in step (b) were taken and put into 5 mL of mixed acid solution for treatment. The system temperature was controlled at 45°C and the magnetic stirring speed was 150 rpm. The acid treatment was carried out for 20 min, and then the microspheres were rinsed with deionized water for 2-3 times to remove the residual acid components. After drying, the acid-modified zeolite microspheres were obtained.

[0071] (d) Catalyst mixing: 7 g of acid-modified zeolite microspheres and 13 g of alumina-supported sulfided Co-Ni hydrogenation were uniformly mixed to obtain a composite catalyst.

[0072] Among them, bio-oil (oleic acid and linoleic acid 73.8wt%, stearic acid and other unsaturated fatty acids 21.3wt%) was obtained from waste cooking oil after filtering and deslagging pretreatment. Palladium mesoporous carbon catalyst (model: Pd102, palladium content 3.5%, specific surface area 350cm 2 / g) is produced by Xi'an Kaili New Materials Co., Ltd. Zeolite particles (specific surface area of ​​780m 2 / g, with a silicon dioxide content of 97.5%) was produced by Chaoyang Xinhe Zeolite Technology Co., Ltd. The pore-forming agent was a mixture of 300-mesh carbon powder and 600-mesh carbon powder in a mass ratio of 1:1. The binder was a mixture of sodium silicate, deionized water, and urea in a mass ratio of 15:1:20. The mixed acid solution was a mixture of 1 mol / L hydrochloric acid and 1.5 mol / L sulfuric acid in a volume ratio of 2:1.

[0073] Comparative Example 1

[0074] The difference between this comparative example and Example 1 is that the acid-modified zeolite microspheres are replaced by an equal amount of zeolite molecular sieve, the model of the zeolite molecular sieve is NKF-A (5A), produced by Tianjin Nanhua Catalyst Co., Ltd., and the rest is the same as Example 1.

[0075] Comparative Example 2

[0076] The difference between this comparative example and Example 1 is that the ferric chloride solution for impregnating the zeolite is replaced by a cupric chloride solution of the same concentration, and the rest is the same as Example 1.

[0077] Performance testing

[0078] Hydrogenated oil conversion test

[0079] Referring to the operation of GB / T7304-2014 and the sampling method of GB / T4756, the oil sample after the reaction was extracted several times in the bio-oil pre-hydrogenation reactor to obtain 125mL of oil sample. The automatic acid value tester (instrument model SYD-264b) was used to automatically control the addition of 0.1mol / L potassium hydroxide isopropanol solution. After the potential stabilized, the amount of titrant was recorded and the potential value at this time was read. At the same time, the same amount of untreated bio-oil was taken for titration test, and the oleic acid content in the treated oil and untreated bio-oil was calculated respectively, and the conversion rate of hydrogenated oil obtained by hydrogenation pretreatment of the oil sample was calculated.

[0080] Conversion rate calculation formula:

[0081] ×100%

[0082] X: Conversion rate (%)

[0083] A0: Oleic acid content in untreated bio-oil (g)

[0084] A: Oleic acid content in the treated oil sample (g)

[0085] Refined oil conversion test

[0086] Referring to the operation of GB / T26636-2011 and the sample preparation method of GB / T15687, take 50 mg of the pre-hydrogenated oil sample and the reacted oil sample in the first fixed bed, add 1-3 mL of tetrahydrofuran, and mix well. Then add 50 mg of anhydrous sodium sulfate and let it stand for 2-5 minutes. Filter with a filter membrane with a pore size of 1 μm, then use a syringe to draw 50-100 μL of sample solution, so that the solution fills the injection loop, control the injection and connect the chromatographic workstation (instrument model: N2000). Calculate the triglyceride content in the two oil samples respectively, and calculate the conversion rate of refined oil obtained by hydrogenation of the oil sample.

[0087] Conversion rate calculation formula:

[0088] ×100%

[0089] Y: Conversion rate (%)

[0090] B0: Triglyceride content in untreated bio-oil (g)

[0091] B: Triglyceride content in the treated oil sample (g)

[0092] Sulfur content test

[0093] Referring to the operation of SH / T0689-2000 and the sampling method of GB / T4756, 10 μL of diluted sample was delivered to the high-temperature combustion tube with a special micro-syringe, and the sample in the combustion tube was heated by electric heating to make it burn completely. The exhaust gas from the combustion chamber was collected, and after removing the water, it was irradiated with ultraviolet light, and then a photomultiplier tube (instrument model: N1013) was used to detect the fluorescence signal, and the sulfur content in the sample was calculated by the signal value.

[0094] Water content test

[0095] Refer to SH / T0246-1992 for operation, prepare the electrolytic cell instrument and configure the electrolyte, use a dry sampling bottle to take the petroleum sample to be tested, inject 5mL of the sample into the electrolytic cell, start the coulometric titrator (instrument model: MKC-710S), and after the electrolysis is complete, calculate the water content in the sample based on Faraday's law of electrolysis and the amount of electricity consumed during the electrolysis process.

[0096] Cetane number test

[0097] Referring to the operation of GB / T386-2021 and the sampling method of GB / T4756, the prepared biodiesel and the same amount of standard fuel are taken from opaque metal cans. The test engine speed is 900r / min±9r / min, the injector opening pressure is 10.30MPa±0.34MPa, and the test instruments are debugged to the specified test conditions. The test is carried out using a cetane number tester (instrument model: RASX-100M). By changing the compression ratio of the engine, the ignition properties of the sample to be tested and the standard fuel for comparison are compared, the sample to be tested is recorded, and the cetane number of the prepared biodiesel is calculated.

[0098] The test results of the performance test experiments of Examples 1-3 and Comparative Examples 1-2 are shown in Table 1 and Attached Figure 2 With attached Figure 3 shown.

[0099] Table 1

[0100]

[0101] Analysis of Examples 1-3 and Comparative Examples 1-2 and Figure 2 It can be seen that the conversion rates of hydrogenated oil and refined oil in Example 2 are the highest, and the oil conversion efficiency using the catalyst compounded in Example 2 is the best.

[0102] Analyze Examples 1-3 and combine Table 1 with Figure 3 It can be seen that the residual sulfur content per kilogram of biodiesel produced in Example 2 is the lowest, indicating that the composite catalyst obtained by the experimental method of Example 2 has the highest catalytic efficiency and the best sulfur absorption effect. The water content of the biodiesel prepared in Example 2 is the highest among Examples 1-3, which may be because the composite catalyst under the experimental method of Example 2 catalyzes the oil most completely, resulting in an increase in the water content generated by hydrodeoxygenation in the product, but the water content in Example 2 is still far less than the test data of Comparative Examples 1-2.

[0103] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing biodiesel from bio-oil, characterized in that: The following steps are involved: (S01) Hydrogenation pretreatment: Bio-oil is mixed with hydrogen and added into a reactor loaded with a composite catalyst to react and obtain hydrogenated oil; (S02) Hydrofining: The hydrogenated oil is mixed with hydrogen and added into the first fixed bed loaded with the composite catalyst to react and obtain refined oil; (S03) Hydroisomerization: The refined oil is mixed with hydrogen and added to the second fixed bed loaded with palladium mesoporous carbon catalyst to react to obtain isomerized oil, which is then fractionated at atmospheric pressure to obtain biodiesel on the distillation line side; The preparation of the composite catalyst comprises the following steps: (a) Zeolite impregnation treatment: immersing zeolite particles in a ferric chloride solution, stirring, and drying to obtain ferric chloride impregnated zeolite; (b) Preparation of zeolite microspheres: ferric chloride impregnated zeolite, a binder, and a pore former are uniformly mixed, granulated, and sintered to obtain zeolite microspheres; (c) Acid modification of zeolite microspheres: adding zeolite microspheres to a mixed acid for treatment, followed by solid-liquid separation, to obtain acid-modified zeolite microspheres; the mixed acid is prepared by mixing 1 mol / L hydrochloric acid and 1.5 mol / L sulfuric acid in a volume ratio of (1.5-2):1; (d) Catalyst mixing treatment: The acid-modified zeolite microspheres are mixed with the alumina-supported sulfided Co-Ni hydrogenation catalyst to obtain a composite catalyst.

2. The method for preparing biodiesel from bio-oil according to claim 1, characterized in that: In the step (a), the zeolite impregnation treatment temperature is set at 45-50°C.

3. The method for preparing biodiesel from bio-oil according to claim 1, characterized in that: In the step (b), the mass ratio of the zeolite impregnated with ferric chloride to the pore-forming agent is (100-110):(1-1.2).

4. The method for preparing biodiesel from bio-oil according to claim 1, characterized in that: In the step (b), the pore-forming agent is carbon powder.

5. The method for preparing biodiesel from bio-oil according to claim 1, characterized in that: In the step (b), the sintering temperature of the zeolite microspheres is set to 600-620° C. and kept at this temperature for 5 hours.

6. The method for preparing biodiesel from bio-oil according to claim 1, characterized in that: In the step (c), the time for the acid modification treatment of the zeolite microspheres is set to 15-20 minutes.

7. The method for preparing biodiesel from bio-oil according to claim 1, characterized in that: In the step (c), the temperature of the acid modification treatment of the zeolite microspheres is set at 40-45°C.

8. The method for preparing biodiesel from bio-oil according to claim 1, characterized in that: In the step (d), the mass percentage of the acid-modified zeolite microspheres in the composite catalyst is 25%-35%.

Citation Information

Patent Citations

  • Method for preparing bio-based long-chain alkane

    CN117660115A

  • Method for preparing biodiesel using tung oil

    CN104560410A

  • Sulfur-containing compound peculiar smell eliminating agent as well as preparation method and application thereof

    CN109701489A